The Need for Hematology Nurse Education in Low- and Middle-Income Countries: A Community Case Study in Tanzania - Buser, Julie M. (Frontiers in Public Health, 2017)
Hematology-related diseases such as anemia, malaria, sickle cell disease and blood cancers have differing rates of survival between high-income and low- and middle-income countries (LMICs). Nurses in LMICs have an unmet need for specialty training and education to address hematology and hemato-oncology disorders. A gap in the literature exists about hematology nurse education and clinical service demands in LMICs. This community case study documents a collaborative hematology and basic hemato-oncology education program to sustainably strengthen nurse capacity at a national referral hospital and university in Tanzania. The goal of the intervention was to provide culturally competent nurse training in pediatric and adult hematology. A certified pediatric nurse practitioner with hematology and oncology experience provided culturally competent training and staff development to nurses over two weeks to meet this goal. Prior to development of a training schedule, nurses confidentially identified five of their top learning needs. Main hematology and basic oncology educational needs identified by nurses were the management of anemia, safe handling of cytotoxic agents, and treatment of sickle cell disease. The format of the education varied from bedside teaching to formal presentations to one-on-one individual discussions. Overall, nurses expressed satisfaction with the education and verbalized appreciation for teaching and training activities tailored to meet their needs. Specialized training in hematology and hemato-oncology has the potential to increase nurses’ confidence, respect and participation in interprofessional team decision making. Lessons learned from the impact of collaborative nurse education and partnership in Tanzania can be generalized to other LMICs. This community case study highlights the importance of specialty nurse education, interprofessional development and global partnerships needed to improve patient outcomes.